The Role of Organizational Culture in Mediating the Improvement of the Performance of the Indonesian Marine Corps - Supardi, Endi; Arafah, Willy; Anggiani, Sarfilianty (Ridwan Institute, 2024)
The study examines specific aspects of organizational performance within the Indonesian Navy (TNI AL), with a particular focus on the Marine Corps, essential for safeguarding Indonesia's maritime sovereignty. Utilizing quantitative methods and a survey approach, data was gathered from middle officers serving across 11 Marine Corps units over the past 5 years. Findings indicate that strategic leadership style, career development, and strategic competence of human resources significantly influence organizational performance within the Marine Corps. These factors, alongside organizational culture, are pivotal in shaping and sustaining performance levels. Importantly, the research underscores the importance of understanding these dynamics for Marine Corps management to enhance performance and achieve long-term objectives, particularly in navigating the complexities of globalization. Additionally, while rooted in the context of the Indonesian Navy, the implications of these findings extend to broader organizational settings, highlighting their potential applicability beyond the specific context of the TNI AL and Marine Corps.